Perceived risk structures the space use of competing carnivores. (11th October 2021) - Rodriguez Curras, Mauriel; Donadío, Emiliano; Middleton, Arthur D; Pauli, Jonathan N
Abstract: Competition structures ecological communities. In carnivorans, competitive interactions are disproportionately costly to subordinate carnivores who must account for the risk of interspecific killing when foraging. Accordingly, missed opportunity costs for meso-carnivores imposed by risk can benefit the smallest-bodied competitors. However, the extent to which the risk perpetuates into spatial partitioning in hierarchically structured communities remains unknown. To determine how risk-avoidance behaviors shape the space-use of carnivore communities, we studied a simple community of carnivores in northern Patagonia, Argentina: pumas ( Puma concolor ; an apex carnivore), culpeo foxes ( Lycalopex culpaeus ; a meso-carnivore), and chilla foxes ( Lycalopex griseus ; a small carnivore). We used multi-species occupancy models to quantify the space use within the carnivore community and giving-up densities to understand the behaviors that structure space use. Notably, we applied an analytical framework that tests whether the actual or perceived risk of predation most strongly influences the space use of subordinate carnivores although accounting for their foraging and vigilance behaviors. We found that there was a dominance hierarchy from the apex carnivore through the meso-carnivore to the subordinate small carnivore, which was reflected in space. Although both meso- and small carnivores exhibited similar predator avoidance behavioral responses to apex carnivores, the habitat associations of apex carnivores only altered meso-carnivore space use. The biases in risk management we observed for meso-carnivores likely translates into stable co-existence of this community of competing carnivores. We believe our analytical framework can be extended to other communities to quantify the spatial-behavioral tradeoffs of risk. Abstract : Carnivores can avoid antagonistic interactions from dominant competitors by using indirect cues of risk. We studied the space use and predator-avoidance behaviors that a meso- and small carnivore utilized to avoid an ambush apex carnivore. We found that meso-carnivores gave up space for safety, which provided small carnivores with spatial opportunities. The biases in predator-avoidance behaviors we observed in meso-carnivores is likely characteristic of the mechanism that allows the co-existence of competing carnivores broadly.